Understanding interventions in ASEAN's non-interference principle - Dewi Asyura Mustajab (Nanyang Technological University, 2022)
‘ASEAN Way’ has been the bedrock of ASEAN for decades, with the non-interference principle being one of the most important aspects of the norms that ASEAN has developed over time. The benefits that ASEAN yield from the non-interference principle is enormous and thus, the association has strong incentives to maintain its strong rhetoric to the principle. Yet, there are circumstances which might make interference inevitable. When is this the case? This paper aims to develop greater understanding of the non-interference principle, how it has shifted over time, and what are the factors behind the violations of the principle. By using the historical institutionalism framework, this paper finds that ASEAN-led interventions would happen if the aggressor came from a weaker country, intervening would not cause an undesirable precedent, international backlash is high, and intervention does not involve military. The findings are subsequently applied to the 2021 military coup that took place in Myanmar.